2008
DOI: 10.1189/jlb.1007676
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 and IFN-γ stimulate mouse macrophages to express BAFF via different signaling pathways

Abstract: B cell-activating factor belonging to the TNF family (BAFF) is primarily expressed by macrophages and dendritic cells and stimulates the proliferation, differentiation, and survival of B cells and their Ig production. In the present study, we examined the pathways by which TGF-beta1 and IFN-gamma induce BAFF expression to see if TGF-beta1 and IFN-gamma regulate B cell differentiation via macrophages. We found that TGF-beta1 stimulated mouse macrophages to express BAFF and that a typical TGF-beta signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 65 publications
6
35
0
Order By: Relevance
“…Between the two pathways, we do not distinguish at the moment which pathway is more relevant to TGFβ1-induced APRIL expression as often demonstrated by others (Hanafusa et al, 1999;Kamaraju and Roberts, 2005;Patel et al, 2010). We have previously shown that TGF-β1 induces the expression of BAFF, another TNF family member, mainly through Smad3/4 signaling (Kim et al, 2008). Thus, the mechanisms underlying APRIL and BAFF induction by TGF-β1 are slightly different, though both molecules are involved in Ig synthesis by B lymphocytes.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Between the two pathways, we do not distinguish at the moment which pathway is more relevant to TGFβ1-induced APRIL expression as often demonstrated by others (Hanafusa et al, 1999;Kamaraju and Roberts, 2005;Patel et al, 2010). We have previously shown that TGF-β1 induces the expression of BAFF, another TNF family member, mainly through Smad3/4 signaling (Kim et al, 2008). Thus, the mechanisms underlying APRIL and BAFF induction by TGF-β1 are slightly different, though both molecules are involved in Ig synthesis by B lymphocytes.…”
Section: Discussionmentioning
confidence: 87%
“…Ig isotype switching is a critical event in B-cell differentiation, and TGF-β1 is a specific switching factor for the IgA and IgG2b mouse isotype (Kim and Kagnoff, 1990;McIntyre et al, 1993). Since we have previously demonstrated that TGF-β1 stimulates mouse macrophages to express BAFF (Kim et al, 2008), it was worthwhile to investigate if TGF-β1 can modulate macrophages to express another member of the same family, APRIL. Indeed, we found that TGF-β1 induced APRIL transcription in the mouse macrophage cell line, P388D1 as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations